Diversity of infectious aetiologies of acute undifferentiated febrile illnesses in south and Southeast Asia: a systematic review - Kinley Wangdi; Kaushalya Kasturiaratchi; Susana Vaz Nery; Colleen L. Lau; Darren J. Gray; Archie C. A. Clements (BMC Infectious Diseases, 2019)
Abstract Background Acute undifferentiated febrile illness (AUFI) is caused by a multitude of diverse pathogens, with significant morbidity and mortality in the developing world. The objective of this review was to characterise the diversity and relative importance of common infectious aetiologies of AUFI in South and Southeast Asia. Methods We conducted a comprehensive literature review to identify common aetiologies of AUFI in Asian countries. Four medical and life sciences databases including PubMed, Medline, Embase and Cochrane Central, and Google Scholar were searched for articles published from January 1998 to March 2019. Results Forty-three studies met the inclusion criteria. Among AUFI cases, viral aetiologies at 18.5% (14888) were more common than bacterial aetiologies (12.9% [10384]). From 80,554 cases, dengue fever was the most common aetiology (11.8%, 9511), followed by leptospirosis (4.4%, 3549), typhoid (4.0%, 3258), scrub typhus (4.0%, 3243) and influenza other than H1N1 (3.1%, 2514). In both adults and children: dengue fever was the leading cause of AUFI with 16.6% (1928) and 18.7% (1281) of the total cases. In admitted patients, dengue fever was the main cause of AUFI at 16.4% (2377), however leptospirosis at 13.9% (2090) was the main cause of AUFI for outpatients. In South Asia, dengue fever was the main cause of AUFI, causing 12.0% (6821) of cases, whereas in Southeast Asia, leptospirosis was the main diagnosis, causing 12.1% (2861) of cases. Conclusions In this study the most common causes of AUFI were viral, followed by bacterial and protozoal (malaria) infections. Dengue was the commonest virus that caused AUFI while leptospirosis and typhoid were important bacterial infectious causes. Therefore, it is imperative to maintain a sound epidemiological knowledge of AUFI so that evidence-based diagnostic criteria and treatment guidelines can be developed.